1983
DOI: 10.4039/ent1151215-9
|View full text |Cite
|
Sign up to set email alerts
|

PROTECTION OF BACILLUS THURINGIENSIS FROM INACTIVATION BY SUNLIGHT

Abstract: The effectiveness of several commercially available sunlight screens in protecting Bacillus thuringiensis Berliner (B.t.) against inactivation by solar irradiation was assessed in the laboratory and field. Spore viability and residual insecticidal activity of B.t. were rapidly reduced by solar radiation in the range of 300 to 400 nm wavelength. The addition of ultraviolet absorbers, Uvinul DS49 and Erio Acid Red, to a Thuricide spray formulation prolonged the insecticidal residual activity on coniferous trees,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…To address the problem of the sensitivity to UV irradiation of spores and d-endotoxin preparation, some chemical screens have been found (Cohen et al, 2001;Dunkle and Shasha, 1989;Morris, 1983). Addition of cationic chromophores such as acriflavine and methyl green, as components of the formulation, can achieve UV-protection.…”
Section: Discussionmentioning
confidence: 99%
“…To address the problem of the sensitivity to UV irradiation of spores and d-endotoxin preparation, some chemical screens have been found (Cohen et al, 2001;Dunkle and Shasha, 1989;Morris, 1983). Addition of cationic chromophores such as acriflavine and methyl green, as components of the formulation, can achieve UV-protection.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, and especially in areas exposed to the sun, the residual effect is very short (Leong et al 1980) and the product has to be reapplied. Photoinactivation seems to be one of the major environment factors affecting the stability of Bti delta-endotoxin (Morris, 1983). Yu-Tien et al (1993) reported that Bti completely lost its toxicity to mosquito larvae when exposed to irradiation at 253nm.…”
Section: Bti Formulationsmentioning
confidence: 99%
“…Red XB100 Morris, 1983Dunkle and Shasha, 1988, 1989 acriflavin, methyl green rhodamine B Cohen et al, 1991, Melanin Liu et al, 1993Ridgway et al, 1996McGuire et al, 1996Behle et al, 1996, 1997 UV .…”
Section: Bt Uvmentioning
confidence: 99%